Primavera islâmica na historiografia africanista - Mota, Thiago Henrique (Afro-Ásia, 2021)
Resenha de: NGOM, Fallou; KURFI, Mustapha H.; FALOLA, Toyin (orgs.). The Palgrave Handbook of Islam in Africa. Londres: Palgrave Macmillan, 2020. 774 p.